Knowledge mapping analysis of the track and hotspot of water lubrication: A scientometrics review - Runzhou Xu; Defa Wu; Zhenyao Wang; Yipan Deng; Qian Cheng; Hao Pang; Wenshu Wei; Yinshui Liu (Friction)
Abstract With the enhancement of environmental protection awareness of the international community and the continuous promotion of green and sustainable development of manufacturing industry, water lubrication instead of mineral oil has become the future development trend due to its green, pollution-free, clean, safe, and sustainable advantages especially in ships, marine, coal mining, and other fields. In recent years, with the rapid development of water lubrication research, significant progress has been made in related research knowledge domain and discipline. A systematic and extensive assessment of water lubrication research has become increasingly important. The objective of this research is to reveal the research status, research hotspots, and development trends in the field of water lubrication. Therefore, CiteSpace was used to conduct a systematic bibliometric and scientometrical analysis of 1,792 publications from Web of Science core collection database (1997–2021). The results show that China and USA are the most productive countries in the field of water lubrication and have made outstanding contributions. Through the analysis of hot key words and co-citation references, this paper reviews the research status of water lubrication in three aspects: (1) lubricating medium modification; (2) material preparation; (3) surface optimization. It has become a research hotspot to promote the superlubricity contact interface and the application of nanotechnology. The results of this study can make a significant contribution to the development of water lubrication by providing a comprehensive understanding of the research status and research hotspots in this field. Personal understanding and discussion of research hotspots and research status are expected to provide insights into future research trends. In addition, this study will provide valuable references and guidelines for researchers who are interested in this field.